HUBUNGAN PENGAMBILAN AIR PADA MATA AIR BEJI DESA DI DESA BAHA DENGAN KEBERADAAN SUBAK BULAN PASEDAHAN YEH SUNGI KECAMATAN MENGWI KABUPATEN BADUNG - I Made Letra; N. Merit; N. Sunarta (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science))
ago. This traditional organization is socio-religious in nature based on the high spirit of cooperativework. It is very effective in support of the development of agriculture in Bali and it serves as an inheritanceof highly noble value so that it deserves to be conserved. Development in globalization and modernizationera indeed starts to push the subak culture either interms of pelemahan, pawongan, and parhyangan. SubakBulan pesedahan of Yeh Sungi Mengwi District Badung Regency whose irrigation water quite depends uponwater source has been disturbed since some of the beji water source of Baha village has been taken by otheruser.This study aims to know the impact of the taking of water from beji water source of Baha villageagainst the availability of irrigation water for Subak Bulan, the perception of subak members for the takingof the water and what is the relationship of the change of use of rice field in the Subak Bulan area with thetaking of water in the water source. The method employed is descriptive and corational method. Datacollecting by means of field observation in every water source and intake, interview with respondents usingquestionnaire for 48 respondents out of 303 Subak Bulan members.The findings show that the availability of irrigation water for Subak Bulan has its source from watersource and some of the water coming from the technical irrigation of Yeh Sungi quite fluctuates caused bythe change of season and the water debit from the upstream irrigation water because the location of SubakBulan is in the most downstream part of the irrigation network of Yeh Sungi. The availability of irrigationwater in each block (munduk) is not optimal. The perception of Subak Bulan to the taking of beji sourcewater of Baha village is that most of the villagers know this and they feel this is disadvantageous to them.There has been a change of land use in the area of Subak Baha as a result of water availability, economic,and social factor from 2000 to 2005 covering the area of 5.25 ha. The relationship between the change ofland use in Subak Baha and the taking of water in beji water source of Baha village shows negativecorrelation which is very significant at- 0.8875 caused by a number of factors among others being the time period for taking the water, opening ofnew roads, lack of water, land opening for settlement.It can be concluded that there is a lack in the availability of irrigation water of Subak Bahainequitably and it fluctuates as a result of the change of season. There is a need for replanning of blocks ofrice fields that need to be irrigated so that the source water of Subak Bulan and the interest of Baha villageare not dissatisfied therefore the source water should be well and fairly managed and preserved. The role ofthe government is also hoped in such a way that it serves as a mediator and makes regulations related to themanagement of the water resources available within the area of Subak Bulan.